SOSIOLOGI HUKUM PENDIDIKAN INDONESIA - Ainun Najib (LP2M Universitas Ibrahimy, 2013)
Embodiment of the mandate of 1945 constitution is the enactment of Law No. 20 Year 2003 on National Education System, which is a product of the first education law in the early 21st century. This law became the legal basis to establish a national education by applying the principles of democracy, decentralization, autonomy and education that upholds human rights. This law is the basis to develop a national education law by applying the principles of democracy, decentralization, autonomy and education that upholds human rights. Since the Declaration of Independence August 17, 1945, the law on the national education system has undergone several changes.Of the many elements of educational resources, the curriculum is one element that can make a significant contribution to the development process of realizing the potential quality of the learners. There is no doubt that the curriculum, which was developed with based on competence is indispensable as an instrument to guide learners who are able to become a qualified human being and proactively meet the challenges of the times which always change and evolving.Conceptually, the curriculum is an educational response to the needs of society and nation in developing its young generation. Pedagogically, educational curriculum is designed to give learners the opportunity to develop his or her potential in a fun learning environment and in accordance with his ability to have the desired quality of society and nation. Legally, the curriculum is a public policy that is based on the philosophical foundations of the nation and judicial decisions in the field of education.